-6u=10-5u

Simple and best practice solution for -6u=10-5u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6u=10-5u equation:


Simplifying
-6u = 10 + -5u

Solving
-6u = 10 + -5u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '5u' to each side of the equation.
-6u + 5u = 10 + -5u + 5u

Combine like terms: -6u + 5u = -1u
-1u = 10 + -5u + 5u

Combine like terms: -5u + 5u = 0
-1u = 10 + 0
-1u = 10

Divide each side by '-1'.
u = -10

Simplifying
u = -10

See similar equations:

| 5.9s=3(-3.4s-15.91) | | 5x+6=16x+-3x+54 | | x-10=104 | | -3(8+n)=33 | | 6(x+1)-2=3x-12 | | 5x+6=16x-3x | | x/14=12 | | 24=1/2(x)*12 | | 11-4(5f+20)=11-16f | | 9-7n+4n=27-69 | | 1+x/8=3 | | 0.8(5x+4)=0.3+-(x-3) | | x^2=23-10x | | -3x-3(4x+3)=66 | | 3p+12=33 | | 6x+3x-6=9x+5 | | -49+5y+7=2(4y-3)-9 | | k/18=6 | | y^2+4*y=-1 | | 3p+12-4=18 | | 15.57+16.9n=17.8n-6(7.3n+16.71) | | B+9=-9+9b-10b | | 0.96=1.2m | | 4x-29y=27 | | 2(3.14)x=56.52 | | -4(-1-3x)+4=80 | | B+9=-9+9n-10b | | 70.00+3.0x=80+1.00x | | y^2+4*y=-13 | | 8(c-5)+7=4+c-37 | | -7p=133 | | 12w-8=16w+21 |

Equations solver categories